Robotic-assisted lung nodule diagnosis and resection - Patel, Priya P.; Patel, Ami; Zollinger, Benjamin; Suzuki, Kei (Frontiers in Oncology, 2025)
In the care of lung cancer patients, early diagnosis followed by timely therapeutic procedures can have a significant impact on overall survival and patient anxiety. While robotic-assisted lung resection is now a widely accepted surgical approach, robotic-assisted bronchoscopy is a more recent diagnostic procedure that improves reach, stability, and precision in the field of bronchoscopic lung nodule biopsy. The ability to combine lung cancer diagnostics with curative-intent surgical resection into a single-setting anesthesia procedure has the potential to decrease costs, improve patient experiences, and most importantly, reduce delays in cancer care. In addition, with the expected adoption of sublobar resection for stage I lung cancer ≤2cm, combining robotic-assisted bronchoscopy with robotic surgery offers a single-setting pathway to take advantage of the precision biopsy and localization technique offered by robotic-assisted bronchoscopy and the precision operation offered by robotic surgery. We herein describe our approach to this single-setting procedure. While limited studies suggest that the combined approach results in shorter overall operative time and cost, we need future work to better characterize the overall operative time, complication rates, long-term oncologic outcomes, and cost analysis.